An Improved Bacterial Test System for the Detection and Classification of Mutagens and Carcinogens - Ames, Bruce N. (1973)
We previously described a set of four strains of Salmonella typhimurium designed for detecting the various types of mutagens, and showed their utility in detecting a wide variety of carcinogens as mutagens. The lipopolysaccharide that normally coats these bacteria is a barrier to penetration of mutagens to the cell membrane. The set of tester strains has been improved by adding a mutation (rfa: deep rough) that results in a deficient lipopolysaccharide. The techniques for using these strains for detecting mutagens are presented and the tests are shown to be extremely sensitive and convenient. The specificity of frameshift mutagenesis is clarified. As adjuncts to the test with the four strains, we describe a test that compares mutagenic killing in deep rough strains with and without DNA excision repair, and a test using forward mutagenesis in a deep rough strain lacking excision repair.